(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the present time due to technical advancement the trend of online shopping is on air. Now the customers mostly prefer the purchase of products online rather than going to market.Online shopping provides an ease to people to buy the products of their choice just sitting at home. They have no need to go to market.But as every coin has two faces, online shopping has its own advantages and disadvantages.